Managing Uncertainty: Company’s Adaptive Capabilities during Covid-19 - Iva Atanassova; Peter Bednar (Complex Systems Informatics and Modeling Quarterly)
The concept of organizational learning receives increasing attention and recognition in recent years as a critical enabler of organizational adaptation, survival, and growth during uncertain times. Our study applies a sociotechnical lens to shed light on the organizational learning processes taking place in 40 various sizes and kinds of UK businesses during the critical, volatile, and unprecedented period – February–May 2021. The study identifies learning antecedents and key organizational context enabling and/or impeding learning processes and follow-up evolution within the studied companies. Our research confirms that in an uncertain environment, companies need to develop and apply ad-hoc learning and quick adaptation practices which are critical for survival and growth, and not standard management practices. The findings suggest, however, that even if employees have capability, not all are able to capture and transform intelligence into learning and apply it at a strategic level, reconfiguring purposefully future operational capabilities to respond to environmental changes, as they are not empowered and supported by the organizational management.